Composite flocculant for sludge dewatering, preparation method and application thereof
By using composite flocculant in sludge dehydration and combining the synergistic effect of inorganic and organic flocculants, the problem of low efficiency of sludge dehydration and pollutant removal in the prior art is solved, and deep dehydration of sludge and effective removal of pollutant substances are achieved.
Patent Information
- Application Number
- CN202410898922.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-07-05
AI Technical Summary
In the prior art, the use of flocculants is not efficient in dehydrating sludge and removing pollutants. Especially when treating municipal sewage with complex components, it is difficult to achieve deep dehydration and reduce filtrate turbidity and COD.
A composite flocculant for sludge dehydration is provided, including inorganic flocculant A and organic flocculant B. Inorganic flocculant A consists of polyferrous silicate, polydiallyldimethylammonium chloride and cerium oxide, while organic flocculant B contains cationic polyacrylamide, activated carbon, wood ash, composite modifiers and catalyst aids. Through the combined use of these flocculants, deep dehydration of sludge and effective removal of pollutants can be achieved.
Through the synergistic action of inorganic and organic flocculants, deep dehydration of sludge is achieved, turbidity and COD of the filtrate are reduced, the efficiency and effect of sludge dehydration are improved, and the problem of low efficiency of sludge dehydration and pollutant removal in the prior art is solved.
Smart Images

Figure CN118791212B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sewage treatment, and in particular to a composite flocculant for sludge dehydration, a preparation method and an application thereof. Background Art
[0002] With the rapid development of my country's economy and the rapid improvement of people's living standards, urban water consumption has continued to increase, and the resulting generation and discharge of sewage and sludge has also increased. At present, my country's annual sludge production has increased by 10%, and it is expected that my country's sludge production will exceed 90 million tons in 2025. The water content of sludge is usually high (more than 80%), and the odor and organic volatiles emitted by high-water-content sludge not only pollute the air, but also pollute groundwater, and cause local sudden excessive heavy metal ions, which are directly harmful to human health after being absorbed by crops.
[0003] In the prior art, mechanical methods or flocculants are usually used to dehydrate sludge, but the separated water produced after sludge dehydration contains various organic and inorganic substances, which will not only make the water turbid, but also have a high content of suspended organic matter, which will pollute the environment. There are four forms of water in sludge: free water in sludge, capillary gap water, adsorbed water that cannot be removed by mechanical action, and bound water inside the sludge, which must be removed by adding flocculants. However, for municipal sewage with complex components and difficult to treat, the use of cationic polyacrylamide flocculants alone often cannot achieve good flocculation and dehydration effects. After flocculation, the moisture content of the dry mud is still high after mechanical dehydration by dehydration equipment. At the same time, the turbidity and COD of the filtrate still exceed the standard and need to be treated before discharge. Therefore, for such municipal sewage with complex components and difficult to dehydrate, providing a composite flocculant that can deeply dehydrate and reduce the turbidity and COD of the filtrate is a problem that needs to be solved in the prior art. Summary of the invention
[0004] The embodiments of the present application provide a composite flocculant for sludge dewatering, a preparation method and application thereof, so as to solve the problem of low efficiency of sludge dewatering and pollutant removal using flocculants in related technologies.
[0005] In a first aspect, a composite flocculant for sludge dewatering is provided, comprising:
[0006] Inorganic flocculant A, comprising 30-40 parts of polysilicate iron, 10-15 parts of polydiallyldimethylammonium chloride, and 5-10 parts of cerium oxide;
[0007] The organic flocculant B comprises 10-15 parts of cationic polyacrylamide, 15-20 parts of activated carbon, 30-40 parts of plant ash, 5-15 parts of composite modifier and 3-6 parts of catalytic aid.
[0008] Preferably, the composite modifier includes polylactic acid and polyvinyl alcohol, and also includes one of glyceryl stearate and ammonium stearate, and in the composite modifier, the mass ratio of polyvinyl alcohol to polylactic acid is 1:1 to 1:3, and the mass ratio of glyceryl stearate or ammonium stearate to polyvinyl alcohol is 1:3 to 1:5.
[0009] Preferably, in the composite modifier, the mass ratio of glyceryl stearate or ammonium stearate, polyvinyl alcohol and polylactic acid is 1:3:6.
[0010] Preferably, the catalytic aid comprises xanthan gum.
[0011] In a second aspect, a method for preparing a composite flocculant for sludge dewatering is provided, which comprises the following steps:
[0012] S1. Preparation of inorganic flocculant A: Mix 30-40 parts of polysilicate iron solution with 10-15 parts of polydiallyldimethylammonium chloride liquid, stir for 20-40 minutes at 25-35° C., add 5-10 parts of cerium oxide, and continue stirring for 20-40 minutes to obtain inorganic flocculant A;
[0013] S2. Preparation of organic flocculant B:
[0014] S201, after mixing 15-20 parts of activated carbon with 30-40 parts of wood ash, add 10-15 parts of cationic polyacrylamide to the first mixture under stirring, mix well, and obtain a first mixture;
[0015] S202, dispersing and dissolving 5-15 parts of the composite modifier in deionized water twice the mass of the composite modifier at 30-50° C., adding the first mixture and 3-6 parts of the catalyst aid under stirring to obtain an organic flocculant B.
[0016] Preferably, S1 further comprises a method for preparing a polysilicate iron solution:
[0017] S101, preparation of polysilicic acid solution: 0.6 mol / L sodium silicate solution and 20% sulfuric acid are mixed in a volume ratio of 4:1 and stirred, and the pH is adjusted to 3-4 with sodium hydroxide and sulfuric acid, and activated for 1-8 hours to obtain a polysilicic acid solution;
[0018] S102, preparation of polysilicate iron solution: adding ferric sulfate to the polysilicate solution at a ratio of 1:1 silicon to iron at a stirring rate of 150-200 r / min, aging for 2-4 hours, and then diluting the solution to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0019] Preferably, it also includes a method for preparing the composite modifier:
[0020] Polyvinyl alcohol and polylactic acid are dispersed in deionized water in a mass ratio of 1:1 to 1:3, heated to 50 to 80°C, glyceryl stearate or ammonium stearate is added in a mass ratio of 1:3 to 1:5 to polyvinyl alcohol, stirred for 30 to 60 minutes, cooled and filtered to obtain a composite modifier.
[0021] Preferably, the average particle size of the activated carbon is 150-180 mesh.
[0022] In a third aspect, there is provided an application of the composite flocculant for sludge dewatering as described above or the composite flocculant obtained by the preparation method as described above in urban sludge dewatering.
[0023] Preferably, the application comprises the following steps:
[0024] Inorganic flocculant A was added to the municipal sludge sample. After flocs appeared in the municipal sludge sample, organic flocculant B was added.
[0025] The beneficial effects of the technical solution provided by this application include:
[0026] The embodiment of the present application provides a composite flocculant for sludge dewatering, a preparation method and an application thereof. The sludge is deeply dehydrated by using an inorganic flocculant and an organic flocculant in combination. The positively charged polysilicate iron and polydiallyl dimethyl ammonium chloride (PDDA) react with the negatively charged sludge to cause the sludge to aggregate. The PDDA effectively removes suspended organic matter and reduces COD. The polysilicate iron bridges the destabilized sludge to form larger flocs. When cerium oxide is adsorbed onto multiple suspended particles, a bridge is formed to connect the originally dispersed suspended particles together, thereby promoting the aggregation of fine particles in the sludge and the formation of flocs, and reducing the gaps and moisture content between the sludge particles. The cationic Polyacrylamide (CPAM) is adsorbed by hydrogen bonds, and the bridging and capturing effect of high molecular weight long chains forms larger flocs. The combination of wood ash and activated carbon effectively reduces the sludge specific resistance, destroys the gel structure formed by PDDA and sludge, and forms a porous skeleton structure, which is beneficial to the removal of deep free water in the sludge. On the one hand, the composite modifier acts as a filter medium in the sludge dewatering process to effectively intercept solid particles and pollutants in the sludge. On the other hand, it modifies the activated carbon to make it have better dispersibility, stability and adsorption performance, and can enhance the adhesion ability to colloidal particles to achieve the dehydration effect. Therefore, it can solve the problem of low efficiency of sludge dehydration and pollutant removal using flocculants in related technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 A flow chart of the method for preparing a composite flocculant for sludge dewatering provided in this application;
[0029] Figure 2 A flow chart of a method for preparing a polysilicate iron solution provided in the present application;
[0030] Figure 3 A flow chart for preparing organic flocculant B provided in this application. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0032] The present invention provides a method for preparing a composite flocculant for sludge dewatering, which comprises the following steps:
[0033] S1. Preparation of inorganic flocculant A: Mix 30-40 parts of polyferric silicate solution with 10-15 parts of polydiallyldimethylammonium chloride liquid, stir for 20-40 minutes at 25-35° C., add 5-10 parts of cerium oxide, and continue stirring for 20-40 minutes to obtain inorganic flocculant A.
[0034] In some embodiments, step S1 further includes the preparation of a polysilicate iron solution, comprising the following steps:
[0035] S101, preparation of polysilicic acid solution: 0.6 mol / L sodium silicate solution and 20% sulfuric acid are mixed in a volume ratio of 4:1 and stirred, and the pH is adjusted to 3-4 with sodium hydroxide and sulfuric acid, and activated for 1-8 hours to obtain a polysilicic acid solution;
[0036] S102, preparation of polysilicate iron solution: adding ferric sulfate to the polysilicate solution at a ratio of 1:1 silicon to iron at a stirring rate of 150-200 r / min, aging for 2-4 hours, and then diluting the solution to an iron ion concentration of 10 ~3 g / ml to obtain a polysilicate iron solution.
[0037] S2. Preparation of organic flocculant B:
[0038] S201, after mixing 15 to 20 parts of activated carbon with 30 to 40 parts of wood ash, add 10 to 15 parts of cationic polyacrylamide to the first mixture under stirring, mix well, and obtain a first mixture;
[0039] S202, dispersing 5 to 15 parts of the composite modifier in deionized water twice the mass of the composite modifier at 30 to 50° C., adding the first mixture and 3 to 6 parts of the catalyst aid under stirring to obtain an organic flocculant B.
[0040] In some embodiments, the preparation method of the composite modifier includes:
[0041] Polyvinyl alcohol and polylactic acid are dispersed in deionized water in a mass ratio of 1:1 to 1:3, heated to 50 to 80°C, glyceryl stearate or ammonium stearate is added in a mass ratio of 1:3 to 1:5 to polyvinyl alcohol, stirred for 30 to 60 minutes, cooled and filtered to obtain a composite modifier.
[0042] In some embodiments, in the composite modifier, the mass ratio of glyceryl stearate or ammonium stearate, polyvinyl alcohol, and polylactic acid is 1:3:6.
[0043] In some embodiments, the catalytic aid includes xanthan gum.
[0044] In some embodiments, the average particle size of the activated carbon is 150-180 mesh.
[0045] In some embodiments, the composite modifier is selected from a combination of glyceryl stearate and glycerol, a combination of ammonium stearate and ethanol, and a combination of methyl stearate ethoxylate and sorbitol.
[0046] In some embodiments, the ratio of stearyl glyceryl to glycerol is 1:2 to 1:3.
[0047] Example 1
[0048] S1. Preparation of inorganic flocculant A: 30 g of polysilicate iron solution and 10 g of polydiallyldimethylammonium chloride liquid were mixed, stirred at 25° C. for 30 min, 8 g of cerium oxide was added, and stirring was continued for 30 min to obtain inorganic flocculant A.
[0049] Wherein, step S1 also includes the preparation of polyferric silicate solution, comprising the following steps:
[0050] S101, preparation of polysilicic acid solution: under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0051] S102, preparation of polysilicate iron solution: at a stirring rate of 180 r / min, the temperature was controlled at 60° C., ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, the mixture was stirred for 20 min, and after aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0052] S2. Preparation of organic flocculant B:
[0053] S201, after mixing 15 g of activated carbon passed through a 160-mesh sieve with 30 g of wood ash, 10 g of cationic polyacrylamide was added to the first mixture under stirring, and the mixture was mixed evenly to obtain a first mixture;
[0054] S202, dispersing 10 g of the composite modifier in 20 g of deionized water at 30° C., adding the first mixture and 3 g of xanthan gum under stirring to obtain an organic flocculant B.
[0055] Further, the preparation of the composite modifier comprises the following steps:
[0056] 6 g of polylactic acid, 2 g of polyvinyl alcohol, and 2 g of glyceryl stearate were dispersed in deionized water, heated to 80° C., stirred for 30 min, cooled, and filtered to obtain a composite modifier.
[0057] Example 2
[0058] S1. Preparation of inorganic flocculant A: 30 g of polysilicate iron solution and 10 g of polydiallyldimethylammonium chloride liquid were mixed, stirred at 30° C. for 30 min, 10 g of cerium oxide was added, and stirring was continued for 30 min to obtain inorganic flocculant A.
[0059] Wherein, step S1 also includes the preparation of polyferric silicate solution, comprising the following steps:
[0060] S101, preparation of polysilicic acid solution: under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0061] S102, preparation of polysilicate iron solution: at a stirring rate of 180 r / min, the temperature was controlled at 60° C., ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, the mixture was stirred for 20 min, and after aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0062] S2. Preparation of organic flocculant B:
[0063] S201, after mixing 15 g of activated carbon passed through a 160-mesh sieve with 30 g of wood ash, 10 g of cationic polyacrylamide was added to the first mixture under stirring, and the mixture was mixed evenly to obtain a first mixture;
[0064] S202, dispersing 10 g of the composite modifier in 20 g of deionized water at 30° C., adding the first mixture and 6 g of xanthan gum under stirring to obtain an organic flocculant B.
[0065] Further, the preparation of the composite modifier comprises the following steps:
[0066] 6 g of polylactic acid, 2 g of polyvinyl alcohol, and 2 g of glyceryl stearate were dispersed in deionized water, heated to 80° C., stirred for 30 min, cooled, and filtered to obtain a composite modifier.
[0067] Example 3
[0068] S1. Preparation of inorganic flocculant A: 40 g of polysilicate iron solution and 15 g of polydiallyldimethylammonium chloride liquid were mixed, stirred at 25° C. for 30 min, 8 g of cerium oxide was added, and stirring was continued for 30 min to obtain inorganic flocculant A.
[0069] Wherein, step S1 also includes the preparation of polyferric silicate solution, comprising the following steps:
[0070] S101, preparation of polysilicic acid solution: under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0071] S102, preparation of polysilicate iron solution: at a stirring rate of 180 r / min, the temperature was controlled at 60° C., ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, the mixture was stirred for 20 min, and after aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0072] S2. Preparation of organic flocculant B:
[0073] S201, after mixing 20 g of activated carbon passed through a 160-mesh sieve with 40 g of wood ash, 15 g of cationic polyacrylamide was added to the first mixture under stirring, and the mixture was mixed evenly to obtain a first mixture;
[0074] S202, dispersing 9 g of the composite modifier in 18 g of deionized water at 40° C., adding the first mixture and 3 g of xanthan gum under stirring to obtain an organic flocculant B.
[0075] Further, the preparation of the composite modifier comprises the following steps:
[0076] 6 g of polylactic acid, 2 g of polyvinyl alcohol, and 1 g of ammonium stearate were dispersed in deionized water, heated to 80° C., stirred for 30 min, cooled, and filtered to obtain a composite modifier.
[0077] Example 4
[0078] S1. Preparation of inorganic flocculant A: 40 g of polysilicate iron solution and 10 g of polydiallyldimethylammonium chloride liquid were mixed, stirred at 35° C. for 30 min, 5 g of cerium oxide was added, and stirring was continued for 30 min to obtain inorganic flocculant A.
[0079] Wherein, step S1 also includes the preparation of polyferric silicate solution, comprising the following steps:
[0080] S101, preparation of polysilicic acid solution: under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0081] S102, preparation of polysilicate iron solution: at a stirring rate of 180 r / min, the temperature was controlled at 60° C., ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, the mixture was stirred for 20 min, and after aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0082] S2. Preparation of organic flocculant B:
[0083] S201, after mixing 20 g of activated carbon passed through a 160-mesh sieve with 30 g of wood ash, 15 g of cationic polyacrylamide was added to the first mixture under stirring, and the mixture was mixed evenly to obtain a first mixture;
[0084] S202, dispersing 10 g of the composite modifier in 20 g of deionized water at 30° C., adding the first mixture and 5 g of xanthan gum under stirring to obtain an organic flocculant B.
[0085] Further, the preparation of the composite modifier comprises the following steps:
[0086] 6 g of polylactic acid, 3 g of polyvinyl alcohol, and 1 g of ammonium stearate were dispersed in deionized water, heated to 80° C., stirred for 30 min, cooled, and filtered to obtain a composite modifier.
[0087] Comparative Example 1
[0088] Preparation of inorganic flocculant A: 30 g of polysilicate iron solution was mixed with 10 g of polydiallyldimethylammonium chloride liquid, stirred at 25° C. for 30 min, 8 g of cerium oxide was added, and stirring was continued for 30 min to obtain inorganic flocculant A.
[0089] Wherein, the preparation of polyferric silicate solution comprises the following steps:
[0090] Preparation of polysilicic acid solution: Under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0091] Preparation of polysilicate iron solution: Under a stirring rate of 180 r / min and a temperature of 60°C, ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, and the mixture was stirred for 20 min. After aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0092] The inorganic flocculant A was used as the flocculant in Comparative Example 1.
[0093] Comparative Example 2
[0094] Preparation of organic flocculant B:
[0095] After mixing 15 g of activated carbon passed through a 160-mesh sieve with 30 g of wood ash, 10 g of cationic polyacrylamide was added to the first mixture under stirring, and the mixture was mixed evenly to obtain a first mixture;
[0096] 10 g of the composite modifier was dispersed in 20 g of deionized water at 30° C., and the first mixture and 3 g of xanthan gum were added under stirring to obtain an organic flocculant B.
[0097] The organic flocculant B is used as the flocculant obtained in Comparative Example 2.
[0098] Comparative Example 3
[0099] S1. Preparation of inorganic flocculant A: 30 g of polysilicate iron solution and 10 g of polydiallyldimethylammonium chloride liquid were mixed, stirred at 25° C. for 30 min, 8 g of cerium oxide was added, and stirring was continued for 30 min to obtain inorganic flocculant A.
[0100] Wherein, step S1 also includes the preparation of polyferric silicate solution, comprising the following steps:
[0101] S101, preparation of polysilicic acid solution: under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0102] S102, preparation of polysilicate iron solution: at a stirring rate of 180 r / min, the temperature was controlled at 60° C., ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, the mixture was stirred for 20 min, and after aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0103] S2. Preparation of organic flocculant B:
[0104] S201. Mix 20 g of activated carbon passed through a 160-mesh sieve with 40 g of wood ash, add 15 g of cationic polyacrylamide to the first mixture under stirring, mix well, add 3 g of xanthan gum, and stir for 30 minutes to obtain an organic flocculant B.
[0105] Inorganic flocculant A and organic flocculant B were used as flocculants in Comparative Example 3.
[0106] Comparative Example 4
[0107] S1. Preparation of inorganic flocculant A: 30 g of polysilicate iron solution and 10 g of polydiallyldimethylammonium chloride liquid were mixed, stirred at 25° C. for 30 min, 8 g of cerium oxide was added, and stirring was continued for 30 min to obtain inorganic flocculant A.
[0108] Wherein, step S1 also includes the preparation of polyferric silicate solution, comprising the following steps:
[0109] S101, preparation of polysilicic acid solution: under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0110] S102, preparation of polysilicate iron solution: at a stirring rate of 180 r / min, the temperature was controlled at 60° C., ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, the mixture was stirred for 20 min, and after aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0111] S2. Preparation of organic flocculant B:
[0112] 10 g of cationic polyacrylamide and 3 g of xanthan gum were mixed evenly to obtain organic flocculant B.
[0113] Inorganic flocculant A and organic flocculant B were used as flocculants in Comparative Example 4.
[0114] Comparative Example 5
[0115] S1. Preparation of inorganic flocculant A: 30 g of polysilicate iron solution and 10 g of polydiallyldimethylammonium chloride liquid are mixed to obtain inorganic flocculant A.
[0116] Wherein, step S1 also includes the preparation of polyferric silicate solution, comprising the following steps:
[0117] S101, preparation of polysilicic acid solution: under magnetic stirring, 20 ml of 0.6 mol / L sodium silicate solution and 5 ml of 20% sulfuric acid were mixed and stirred, and the pH was adjusted to 3.5 with sodium hydroxide and sulfuric acid, and activated for 7 hours to obtain a polysilicic acid solution;
[0118] S102, preparation of polysilicate iron solution: at a stirring rate of 180 r / min, the temperature was controlled at 60° C., ferric sulfate was added to the polysilicate solution at a silicon-iron ratio of 1:1, the mixture was stirred for 20 min, and after aging for 3 h, the solution was diluted to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
[0119] S2. Preparation of organic flocculant B:
[0120] S201, after mixing 15 g of activated carbon passed through a 160-mesh sieve with 30 g of wood ash, 10 g of cationic polyacrylamide was added to the first mixture under stirring, and the mixture was mixed evenly to obtain a first mixture;
[0121] S202. Add 3 g of xanthan gum to the first mixture under stirring to obtain an organic flocculant B.
[0122] Inorganic flocculant A and organic flocculant B are used as flocculants in Comparative Example 5.
[0123] Specifically, the types and amounts of reagents added in Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Tables 1 to 3.
[0124] Table 1 Types of reagents added in Examples 1 to 4
[0125]
[0126] Table 2 Amount of reagents added in Examples 1 to 4
[0127]
[0128] Table 3 Types of reagents added in Comparative Examples 1 to 5
[0129]
[0130] The present application also provides an application of a composite flocculant for sludge dewatering in urban sludge dewatering, wherein the composite flocculant for sludge dewatering is prepared by the above-mentioned preparation method.
[0131] Specifically, the application includes adding an inorganic flocculant A to a municipal sludge sample, and then adding an organic flocculant B after flocs appear in the municipal sludge sample.
[0132] Inorganic flocculant A and organic flocculant B were diluted to 1‰ respectively, and inorganic flocculant A was added to the municipal sludge sample first. Since the sludge is negatively charged, the positively charged polysilicate iron and PDDA will react with the sludge to neutralize it, causing the sludge to aggregate and coagulate, especially the charged small particles are almost all aggregated. In particular, PDDA can effectively remove suspended organic matter in the water and effectively reduce the COD of the water body. The long chain structure of polysilicate iron will further bridge the destabilized sludge to form larger flocs; at the same time, when cerium oxide is adsorbed on multiple suspended particles, it forms a bridge to connect the originally dispersed suspended particles together, promote the coagulation of fine particles in the sludge and the formation of flocs, reduce the gaps and moisture content between sludge particles, and thus reduce the specific resistance of the sludge.
[0133] After the sludge is initially coagulated and small flocs appear, add organic flocculant B. The plant ash in organic flocculant B can effectively reduce the sludge specific resistance, improve the sludge structure, destroy the gel structure formed by PDDA and sludge, and form a porous skeleton structure, which is conducive to the removal of deep free water in the sludge. CPAM forms larger flocs through hydrogen bond adsorption and the bridging and netting effect of high molecular weight long chains; the composite modifier acts as a filter medium during the sludge dehydration process, effectively intercepting solid particles and pollutants in the sludge, while promoting the rapid discharge of water. On the other hand, it modifies the activated carbon, making it have better dispersibility, stability and adsorption performance, making it easier to interact with water and solid particles in the sludge, achieving better adsorption effect, enhancing the adhesion ability of colloidal particles, and producing better entanglement and flocculation effects. After the dehydration equipment, it can be more effectively dehydrated.
[0134] The flocculants prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were tested for performance through the application:
[0135] The sludge from the thickening tank of a municipal sewage treatment plant was selected as the municipal sludge sample. The inorganic flocculant A and the organic flocculant B were diluted to 1‰ respectively, and added to the sample in a mass ratio of 1:100 in turn to detect the sludge concentration and COD. Specifically, a plate and frame filter press was selected, the pressure was set to 0.6MPa, the filtration time was 30min, and the mud cake and filtrate after filtration were taken out for testing. The turbidity of the filtrate was measured by a turbidity meter (equipment model HACH-2100Q), the moisture content of the mud cake was measured by a moisture meter (equipment model TL211-HE53), and the sludge specific resistance tester (equipment model HAD-TG-250) was used to test the sludge specific resistance. COD was determined by the laboratory in accordance with GB11914-89.
[0136] The specific experimental data are shown in Table 4.
[0137] Table 4 Treatment results of municipal sludge samples in Examples 1 to 4 and Comparative Examples 1 to 5
[0138]
[0139] It can be seen that Examples 1 and 2 are superior to the control sample in terms of mud cake moisture content, filtrate turbidity and COD, and sludge specific resistance, indicating that the components of the flocculant provided by the present invention act synergistically, so that the flocculant has better dehydration performance.
[0140] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A composite flocculant for sludge dewatering, characterized in that: It includes: Inorganic flocculant A, comprising 30-40 parts of polysilicate iron, 10-15 parts of polydiallyldimethylammonium chloride, and 5-10 parts of cerium oxide; Organic flocculant B, which includes 10-15 parts of cationic polyacrylamide, 15-20 parts of activated carbon, 30-40 parts of plant ash, 5-15 parts of composite modifier, and 3-6 parts of catalyst aid; The composite modifier includes polylactic acid and polyvinyl alcohol, and also includes one of stearyl glyceride and ammonium stearate, and in the composite modifier, the mass ratio of polyvinyl alcohol to polylactic acid is 1:1 to 1:3, and the mass ratio of stearyl glyceride or ammonium stearate to polyvinyl alcohol is 1:3 to 1:5; The catalyst aid includes xanthan gum.
2. The composite flocculant for sludge dewatering according to claim 1, characterized in that: In the composite modifier, the mass ratio of glyceryl stearate or ammonium stearate, polyvinyl alcohol and polylactic acid is 1:1:
3.
3. A method for preparing a composite flocculant for sludge dewatering as claimed in any one of claims 1 to 2, characterized in that: It includes the following steps: S1. Preparation of inorganic flocculant A: 30-40 parts of polysilicate iron solution and 10-15 parts of polydiallyldimethylammonium chloride liquid are mixed, stirred at 25-35° C. for 20-40 min, 5-10 parts of cerium oxide are added, and stirring is continued for 20-40 min to obtain inorganic flocculant A; S2. Preparation of organic flocculant B: S201, after mixing 15 to 20 parts of activated carbon with 30 to 40 parts of wood ash, add 10 to 15 parts of cationic polyacrylamide to the first mixture under stirring, mix well, and obtain a first mixture; S202, dispersing 5 to 15 parts of the composite modifier in deionized water twice the mass of the composite modifier at 30 to 50° C., adding the first mixture and 3 to 6 parts of the catalyst aid under stirring to obtain an organic flocculant B.
4. The method for preparing a composite flocculant for sludge dewatering according to claim 3, characterized in that: The S1 also includes a method for preparing a polyferric silicate solution: S101, preparation of polysilicic acid solution: 0.6 mol / L sodium silicate solution and 20% sulfuric acid are mixed in a volume ratio of 4:1 and stirred, and the pH is adjusted to 3-4 with sodium hydroxide and sulfuric acid, and activated for 1-8 hours to obtain a polysilicic acid solution; S102, preparation of polysilicate iron solution: adding ferric sulfate to the polysilicate solution at a ratio of 1:1 silicon to iron at a stirring rate of 150-200 r / min, aging for 2-4 hours, and then diluting the solution to an iron ion concentration of 10 -3 g / ml to obtain a polysilicate iron solution.
5. The method for preparing a composite flocculant for sludge dewatering according to claim 3, characterized in that: It also includes a method for preparing the composite modifier: Polyvinyl alcohol and polylactic acid are dispersed in deionized water in a mass ratio of 1:1 to 1:3, heated to 50 to 80°C, glyceryl stearate or ammonium stearate is added in a mass ratio of 1:3 to 1:5 to polyvinyl alcohol, stirred for 30 to 60 minutes, cooled and filtered to obtain a composite modifier.
6. The method for preparing a composite flocculant for sludge dewatering according to claim 3, characterized in that: The average particle size of the activated carbon is 150-180 meshes.
7. Use of the composite flocculant for sludge dewatering as claimed in any one of claims 1 to 2 or the composite flocculant for sludge dewatering obtained by the preparation method as claimed in claim 3 in dewatering of municipal sludge.
8. The use according to claim 7, characterized in that The application comprises the following steps: Inorganic flocculant A was added to the municipal sludge sample. After flocs appeared in the municipal sludge sample, organic flocculant B was added.
Citation Information
Patent Citations
Efficient low-chloride conditioner and application thereof to dehydration of high-solid-content digested sludge
CN107162383A
Sludge chemical conditioning deep dewatering method
CN108358431A